Establishing the influence of sunflower oil quality indicators on the efficiency of the transesterification catalyst - Korchak, Mykola; Knysh, Vladyslav; Shostia, Anatolii; Usenko, Svitlana; Hmelnitska, Yevgenia; Rachynska, Zoja; Viaskov, Volodymyr; Kostenko, Ivan; Glavatchuk, Vita; Zygin, Sergii (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the process of chemical transesterification of sunflower oil with increased mass fraction of moisture and acid value. Transesterification technology allows obtaining fats with the necessary physico-chemical properties without changing the fatty acid composition. The problem of using alkaline catalysts is rapid deactivation under the influence of impurities present in the fatty raw material. The greatest influence is exerted by moisture and fatty acids. Transesterification of sunflower oil with increased mass fraction of moisture and acid value in the presence of potassium glyceroxide, which is more resistant to deactivating impurities, was studied. Oil parameters: peroxide value 0.18 ½ O mmol/kg, acid value 0.08 mg KOH/g, mass fraction of moisture 0.05%, crystallization temperature –18.38°C. Oil samples with mass fractions of moisture from 0.1 to 0.75% (obtained by adding water) were stored for two months under the following conditions: temperature (20±2) °C, air humidity not more than 70%. After storage, the acid value was measured in each sample and transesterification was performed. The efficiency of the process was assessed by the oil crystallization temperature. The maximum values of oil indicators at which the potassium glyceroxide catalyst is effective were established: mass fraction of moisture 0.4%, acid value 0.28 mg KOH/g. At the same time, the crystallization temperature of sunflower oil is –3.95°C, which corresponds to the maximum increase in the crystallization temperature of oil as a result of transesterification. The results obtained make it possible to effectively transesterify sunflower and other types of non-standard quality oils without preliminary treatment. This will reduce the cost of production and increase the profitability of enterprises (depending on the indicators of non-standard raw materials).